CODESRIA Bulletin Online, No. 6, February 2021: The Gilgamesh Dilemma in Counterbalancing Power in Ghana: Constraints, Opportunities and Possibilities - Clement Sefa-Nyarko (CODESRIA Bulletin, 2021)
Over a period of less than ten years, Ghana’s apex court, the Supreme Court, has adjudicated over two major electoral disputes—in 2013 and 2021—between the two major political parties in the country, the New Patriotic Party (NPP) and the National Democratic Congress (NDC). These rulings have come on the heels of almost three decades of successful institutional design, which was implemented in 1992 in the form of the Fourth Republic. The Fourth Republic was established to bring stability to the nation, after many bouts of chaotic identity-driven politics, coup d’états, foreign interference and general governance deficit, factors that had reinforced each other and had undermined the dignity of its citizens for decades. Today, although identity politics is still prevalent among certain sociocultural groups (especially among Asantes in the Ashanti Region and Ewes in the Volta Region, who form up to 25 per cent of eligible voters) and socioeconomic inequality is still high (the Gini Index in 2016 was 43.5 per cent, meaning only about half of the population share all the country’s wealth), Ghana’s Fourth Republic is still a good example of a stable political regime in Africa. Its greatest weakness, however, lies in the Constitution’s emphasis on checks and balances (in counterbalancing power) within the top tiers of government. In this essay, I argue that this accountability arrangement has nurtured the ‘Gilgamesh’ problem of a top-level conspiracy that undermines systems of accountability in Ghana. I also critique the notion that Ghana’s constitutional arrangement is cast in stone; on the contrary, each moment in the political process offers windows of opportunity to make changes as much as it shuts out other possibilities. In addition, civil society has a role to play in keeping governments accountable, and therefore the interplay between the various arms of government and the citizens must be nurtured constantly. Until the 1990s, Ghana struggled to sustain political stability, swinging from authoritarian regimes in many forms (such as the pre-1951 colonialism, the one-party state in 1962, military dictatorships in the late 1960s and most of the 1970s and 1980s) to the civilian rule of the First, Second and Third Republics, which were mostly unsuccessful in achieving long-term legitimacy. Each era made trade-offs between social identities, opportunities, incentives and political participation. Its current institutional remedy—the Fourth Republic—follows what Reilly (2001: 7) referred to as centripetalism, since it encourages moderation in social identities in party politics and emphasises a unitary national identity. This is in contrast to, say, Ethiopia’s ethnofederalism or Nigeria’s federation, which legitimise distinct regional identities (centrifugalism) within the broader federal architecture. Also, unlike South Africa’s post-apartheid institutional design, which was deliberate and originated from committee-room compromises, Ghana’s Fourth Republic evolved organically from previous political, social and economic catastrophes. Since 1992, the country has had eight relatively peaceful transitions of political power and four changes of government. So, what is the basis of Ghana’s apparently robust design? Two main drivers of Ghana’s political stability have been its ability to successfully tame wide-ranging social identities within party politics (Sefa-Nyarko 2020) and to counterbalance power in response to motivational complexities. It has done this by institutionalising measures that address the tension between self-seeking impulses, principles and altruistic motives (Goodin 1996). According to Robert Goodin (1996:19), institutions are ‘organised patterns of socially constructed norms and roles, and socially prescribed behaviours expected of occupants of those roles’, which are simulated to exert power and influence. One of the three principles of a good institution, as proposed by Goodin, is a sensitivity to motivational complexity. As Mahmood Mamdani (1996) argues, the self-seeking impulses of individuals and groups can be resolved through counterbalancing power between government, civil society and ordinary people. Generally, the counterbalancing of power generates an organic system of accountability, and one of its modus operandi is the Kantian Publicity Principle—the assumption that only publicly defensible actions are permissible and that people would proudly admit their higher motives, but not their lower motives, in public (see Luban 1996). The Government of Ghana’s Fourth Republic has three arms—executive, legislature and the judiciary— each of which must check the other through legislation, constitutional instruments, judicial protocols and administrative processes (Republic of Ghana 1992). There is also civil society, which has established itself as a formidable force in creating equilibrium in the balance of power. Since civil society took shape in Ghana in the 1970s, it has perpetually exerted pressure on successive governments, from Kutu Acheampong’s military-police alliance and throughout Hilla Limann’s Third Republic to Jerry Rawlings’ two military regimes— the Armed Forces Revolutionary Council (AFRC) and the Provisional National Defence Council (PNDC). Civil society has manifested itself in many forms, such as the media, occupational groups, student’s unions, sector-specific groups, issue-based groups, think tanks and academia. Public demonstrations and protests, such as the 1995 Kume Preko outcry against the introduction of Value Added Tax, the 1993 Stolen Verdict campaign and pro-democracy demonstrations that shaped institutional design in the 1970s and 1980s, found legitimacy in the 1992 Constitution (Article 21(1)(d)). The Public Order Act, 1994 (Act 491, amended in 2016) reinforced this constitutional provision, even if some of its clauses, such as the requirement of police clearance for public demonstrations, have been widely criticised due to the risk of abuse by public officials in order to intimidate protesters. Citizens exercising their individual rights also have agency through their participation in regular presidential, parliamentary and local assembly elections. Furthermore, the downstream distribution of executive and administrative authority through the Local Government Act, 1993 (Act 462, amended in 2016), legitimised by Articles 240-256 of the 1992 Constitution, has expanded public participation in governance and counterbalanced central authority. Additionally, the inclusion of Article 55 in the Constitution, which forbids the expression of ethnic, religious or sectarian sentiments in party politics, has been widely credited for sustained political stability in Ghana (Arthur 2009; Sefa-Nyarko 2020). International development agents like the World Bank and IMF, and bilateral agreements, have played a role, too. They have used what Pettit (1996) referred to as ‘filters’, or conditionalities, to counterbalance power in Ghana—and Africa in general—since the end of colonialism and the rise of neoliberalism in the late 1970s. When Ghana’s economy was in near collapse in the 1980s, it was the conditionalities associated with the IMF’s and World Bank’s Economic Recovery Programme, and the infamous Structural Adjustment Programme, that complemented pressure from civil society for the country’s return to constitutional rule in 1992. However, these conditionalities also compounded the crisis of breakdown and consensus in Africa, especially their capitalist, Eurocentric and often condescending and unrealistic motives (Grindle 2004; Kjær 2014; Mkandawire 2010). But Ghana’s ‘institutional design’ also reinforces power imbalances Undoubtedly, as philosophised by Thomas Hobbes, some central authority is required in the architecture of the state (the Leviathan) to ensure co-ordination, leadership and the provision of public goods and services. Ghana has such authority and associated legitimacy set up in its three arms of government. But, left unchecked, the state often abuses its power to extract value from society in ways that exploit and undermine individual liberties. So who determines the level and scope of checks and balances, and how should these be verified? An outcome in the ancient Sumerian Epic of Gilgamesh (c. 1800 BCE) well describes the dilemma of the current power imbalance in Ghana. In this story, the new hero, Enkidu, who is created by the sky god, Anu, in response to the supplications of the people of the city of Uruk to counter the tyranny of King Gilgamesh, eventually sides with Gilgamesh. They combine forces to topple the gods and further undermine the interests of the people. In other words, checks and balances that originate from within the state (at the top) are not enough to protect the interests of society (at the bottom). Accountability must be claimed by society because the state will not willingly offer it, and even if it does, it is rarely in the interest of society. Ghana’s constitutional provisions of checks and balances are only as good as civil society and other non-state actors are active, enduring and vigilant. Although Ghana has a vibrant civil society, a lot more needs to be done because the tension between state and society engenders constant tussle. The Gilgamesh outcome prevails in Ghana’s Fourth Republic because the three arms of government can work together to undermine public interest, and often have done so. Here are some examples. First, the executive and legislature conspired to reduce the potency of the Right to Information Law, 2019 (Act 989) in exerting transparency and social accountability. The genesis of the RTI law was the inability of the Institute of Economic Affairs, a private entity, to access exchange rate data from the Bank of Ghana in the late 1990s. This moved it to sponsor the draft of the RTI bill for Parliament’s consideration (CHRI 2019). This was an attempt by a non-state actor to enforce the operationalisation of the freedom of information provision of Article 21(1)(f) of the 1992 Constitution. The legislature and the executive received the bill in good faith in the early 2000s. However, by the time they passed it into law in 2019, thirteen exemption clauses had been inserted (Sections 5-17) that rendered the law toothless in extracting relevant public information for social accountability. Parliamentary and executive privileges, public safety and national security were some of the reasons cited for these exemptions. Even international actors appeared to be part of this conspiracy. For instance, Section 8(1)(d)(i-ii) of the law disallows the disclosure of information relating to international transactions made by the state. According to this exemption, it is illegal to: reveal information communicated in confidence by a public institution to (i) another public institution in another country or another government, or (ii) an international organisation or a body of that organisation (Republic of Ghana 2019) Even though civil society initiated the RTI process with specific social accountability interests in mind, the legislature and executive took almost two decades to pass it into law, and by the time this was done, the substance of the document had been watered down, making it an ineffective tool to tackle corruption in public spaces. Obviously, the government was incapable of checking itself. Second, the constitutional requirement of Article 78 that mandates the president to appoint the majority of ministers of state from among members of Parliament (MPs) adds to the Gilgamesh problem. This is because the executive and the legislature often conspire to grease each others’ palms, so to speak. Parliamentarians act to please the executive, in order to get ministerial appointments, and the executive is almost certain that Parliament will look the other way when it makes submissions to it. In almost all cases, budgets, bills and contracts that the executive submits to Parliament receive parliamentary approval, often with minor or no revisions. For instance, in 2020 the mous1 Agyapa Minerals Royalties Investment Agreement, which was found to be capable of perpetually robbing the state2 of its mineral resources, received parliamentary approval without a hint of opposition from MPs. It was only when civil society rang the alarm about the inherent financial loss that would accrue to the state that the executive eventually abrogated the deal, which was meant to take its legitimacy from the Minerals Income Investment Fund, 2018 (Act 978). The deal had slipped through Parliament unopposed because of the close link between the two arms of government and legitimised opacity in some financial transactions of state (Kuditchar 2021). Even when the Auditor General and the Special Prosecutor attempted to intervene in matters of public interest in 2020, the former was hunted down and forced to go on leave,3 and the latter tained frustration.4 The deal also nearly succeeded because, throughout the period of the Fourth Republic, the ruling parties often had the majority of MPs to do government’s bidding. However, this majoritarian exercise of power could change. In January 2021, the 8th Parliament was sworn into office after neither the ruling NPP nor the main opposition party, the NDC, had a clear parliamentary majority– each had 137 of the 275 seats. But this expectation is too ambitious precisely because of the manifestation of the Gilgamesh problem. The equal number of ruling and opposition MPs in Parliament ordinarily should be a positive sign for enhanced checks and balances in Ghana, for two reasons. One, citizen voters have become more discerning over time and have moved on from the usual ideological fixations to issue-based political decision-making, and now vote for presidential and parliamentary candidates from different political parties in one election. This political decision-making is termed ‘skirt and blouse’ in local parlance. It signals to politicians that elections are votes of confidence and not a mere census of political affiliation. Two, in the new Parliament, it will be harder for the executive to get its laws, budgets and programmes rubber-stamped, since it will have to convince ruling and opposition MPs about the socioeconomic value of its programmes. However, there are flaws in each of these two arguments. First, voting patterns among almost a quarter of the voting population (Asantes in the Ashanti Region and Ewes in the Volta Region) have not changed since 1992, despite the provisions of Article 55. The votes gained by the NPP in the Asante Region since 1992 continue to increase—from 61 per cent (1992) to 66 per cent (1996), 75 per cent (2000), 75 per cent (2004), 72 per cent (2008), 76 per cent (2016) and 73 per cent (2020)—while in the Volta Region the NPP received an average of only 11 per cent over the same period. Conversely, the NDC claimed an average of 87 per cent of votes in the Volta Region between 1992 and 2020, and managed only 27 per cent on average in the Asante Region (Sefa-Nyarko 2020). In the 2020 election, classified as a pacesetter due to informed political decision-making, the NDC maintained its lead in the Volta Region with 85 per cent of votes, while the NPP got 15 per cent in that region (Electoral Commission Ghana 2020). Similar patterns of unflinching support have been recorded in the three northern regions and among some Akan groups, although voters in the cosmopolitan national capital, the Greater Accra Region, have remained the arbiters of change throughout the Fourth Republic. This suggests that institutional design, even in its most effective form, cannot displace informal arrangements, and Article 55 has been only partially successful in taming sociocultural identities in party politics. Second, any top-down counterbalancing arrangement is counterproductive without the sustained involvement of ordinary citizens. MPs in the Fourth Republic have been found to easily agree on things that are of interest to them, like salary and bonus adjustments, which are often not aligned with wider society’s interests. They have also been found to approve certain laws and contracts that have not stood up to public criticism, such as the Right to Information Law and Agyapa Minerals Royalty Investment Agreement. It is therefore foolhardy to believe that, on their own, MPs would be able to improve checks and balances. At best, governing and opposition MPs might collaborate to achieve goals other than those of public interest. At worst, they are likely to bicker, stalling government business and undermining the ruling government programmes, just as the Parliament of the Third Republic did under the Hilla Limann government. Rawlings’ second coup d’état eventually toppled that government on the grounds that it was incompetent in meeting the needs of the people. Similarly, not working in the public interest could potentially spell doom for the Fourth Republic. Civil society ought to be consistent in showing interest in the affairs of the state, and explore legitimate means of contributing to public discussions, even as the party numbers in Parliament have the potential to strengthen collaboration among MPs or bring the country to a standstill. The judiciary has not been unblemished either. The 2015 Anas Aremyaw Anas’ exposé showed that the judiciary, just like all other arms of government in Ghana, cannot behave without the critical eyes of society on it. In this scandal, judges and lawyers were found to have conspired against unsuspecting victims on trial, taking bribes and aborting justice (Sefa-Nyarko 2015). Judicial reforms followed, which appear to be far reaching, but it cannot be assumed that they will institute greater fairness since the justice system is shielded and its processes are still shrouded in secrecy. There is no doubt that the judiciary still enjoys some legitimacy, as evidenced in the 2021 election arbitration between the NPP and the NDC at the Supreme Court. But this legitimacy is part of a process that must constantly be monitored. It is not an end in itself. Implications The formal structures of state are only effective and responsive to society if society itself is proactive in purposefully engaging with the state. Hayek (1989) has been critical of the state’s capacity to be magnanimous and disciplined, which is true only if society fails to monitor, engage, disagree, contest and co-operate with the state when necessary (Acemoglu and Robinson 2019). Such collaboration between the state and society will not be delivered on a silver platter, as the state is designed to dominate society, and will do so if not restrained by society with focus and purpose. Ghana’s institutional design has been largely successful because of the interaction between the state and society. But this status is not static, it has flaws, and as a work in progress it requires consistent discourse, appraisal and reform. As seen in this essay, an important driver of such reforms and self-reflection is civil society. But civil society itself is problematic. The concept of civil society seems self-explanatory, as an autonomous and objective body that represents the interest of a constituency and functions independently of the state to exert principles of democracy, representation and accountability (Botchway 2018; Hutchful 1995). This is what Kasfir (1998: 1) referred to as the ‘conventional view of civil society’ (see also Whitfield 2003: 381). While this is true, it is a simplistic understanding of civil society, and ignores the complexities of engagements within itself and interactions with governments, donors, international development agencies and organised social groups in the pursuit of subjective interests. The shape, form and process of civil society engagement in Ghana’s state-building has evolved dramatically since the late colonial era. The modern nation emerged as an uncoordinated coalition of farmers, traders, school-leavers and an educated class negotiated with colonial authorities in the 1920s and 1930s. By the middle of the twentieth century, it had become a pawn in the hands of new African political leaders advancing a nationalist agenda. The debilitating socioeconomic conditions of the 1970s and the PNDC government’s acceptance of the World Bank’s Economic Recovery Programmes in the 1980s were catalysts for civil society to mobilise as non-state actors in various forms. In the Fourth Republic (post-1992), civil society has had a more stable and predictable role in political participation and governance than in previous epochs (Botchway 2018; GyimahBoadi 1991). Nevertheless, the idea and practice of civil society are still in flux, and it would be naïve to assume that civil society organisations (occupational and functional groups) and civil society institutions (tertiary institutions, the mass media, faith-based organisations and issue-based advocacy groups) are a flawless collection of people and institutions who have an egalitarian agenda. Yet, without civil society and citizens in general, counterbalancing power is only a textbook exercise. While the Gilgamesh threat remains in Ghana, civil society is the best catalyst for counterbalancing power, despite its shortcomings. The greatest strength of civil society lies in its decentralising tendencies. The media, for instance, ought to continue sharing information and engaging with public officials at all levels—community, district, regional, national and international. A similar strategy of societywide advocacy, information-sharing and social accountability must be employed by all other non-state actors, lest the Gilgamesh problem infest their ranks too. Notes https://graphic.com.gh/news/general-news/agyaparoyalties-deal-to-go-back-toparliament.html https://www.transparency.org/en/blog/ghana-what-is-going-onwith-the-controversial-agyapagold-royalties-deal https://graphic.com.gh/news/general-news/domelevoresponds-to-akufo-addo-sdirective-to-proceed-on-leave.html https://graphic.com.gh/news/politics/why-martin-amiduresigned-as-special-prosecutor.html